Effect of potash alum nano on the efficiency of the photovoltaic cell - Jamil Taghreed N.; Khalaf Ali J.; Neamah Hussein Narimann; Abid Abojassim Ali (E3S Web of Conferences)
With the increasing demand for renewable energy and improving the efficiency of solar cells, it has become necessary to search for materials that help enhance the efficiency of converting light energy into electricity, one of these materials is potash alum. This study aims to study the effect of using Potash alum on the efficiency of the solar cell. The results showed that adding potash alum contributed to significantly improving the efficiency of the solar cell. This study confirms that potash alum can be a pivotal element in improving the efficiency of the solar cell and increasing energy production. The original efficiency of the PV cell was 18.05%. After using potash alum, the efficiency increased to 29.54% at a concentration of 7 mol/l, with a maximum current (I_max) of 42.73 mA and a maximum voltage (V_max) of 4.402 V, and a fill factor (FF) of 0.753.